Impact of Performance Appraisal System and Motivation on Employee Performance - Malik, Nouman; Siddique, Kashif; Amanulla (Social Science Review Archives, 2025)
The current research explains the relationship of employee performance and its antecedents. The main aim of this study is to find the impact of performance appraisal system and motivation on employee’s performance. The quantitative research methodology adopted to achieve the research objectives. Data collected through questionnaire based survey from 97 respondents. The performance appraisal system and motivation have been latent constructs and employee performance as dependent variable. The reliability and validity of constructs measured through composite reliability, Cronbach’s Alpha, factor loadings, and average variance extracted respectively. Partial Least Squares-Structure Equation Modeling (PLS-SEM) technique used to analyze the path model. PLS-SEM is used for different calculation and model evaluation. The current research finds that that performance appraisal system has positive and significant impact on employee performance, while motivation has no impact on employee performance. Future studies may examine employee training and development, communication, work load, burnout and employee engagement as antecedents of employee performance in firms.